Consumer Intervention Mapping—A tool for designing future product strategies within circular product service systems - Sinclair, Matt; Sheldrick, Leila; Moreno, Mariale; Dewberry, Emma (MDPI, 2018)
Re-distributed manufacturing presents a number of opportunities and challenges for New Product Development in a future Circular Economy. It has been argued that small-scale, flexible and localised production systems will reduce resource consumption, lower transport emissions and extend product lifetimes. At the same time smart products within the Internet of Things will gather and report data on user behaviour and product status. Many sustainable design tools have previously been developed but few are able to imagine and develop visions of how future sustainable product service systems might be manifested. This paper introduces the concept of Consumer Intervention Mapping as a tool for creating future product strategies. The tool visualises the points within a product’s lifecycle where stakeholders are able to intervene in the product’s expected journey. This perspective enables the rapid construction of scenarios that explore and describe future circular product service systems. Validation of the tool in three workshops is described and the outcomes are presented. Consumer Intervention Mapping is successful in creating scenarios that describe existing product service systems and new product concepts adapted to a Circular Economy paradigm. Further work is required to refine the tool’s performance in more focused and reflective design exercises.
Keywords: circular design; circular economy; product lifecycle; intervention mapping; scenario matrix; sustainable futures